2006
DOI: 10.1007/s10803-006-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function in Preschoolers with Autism: Evidence Consistent with a Secondary Deficit

Abstract: Recent research on executive function (EF) deficits in autism has led investigators to conclude that EF deficits are secondary to the disorder. The current study has two major goals: (1) Examine whether specific EF deficits are present in the youngest autism group to date (mean = 2.9 years), and (2) examine whether such deficits are secondary to autism, or act as an early non-specific cognitive risk factor for autism by comparing EF abilities of this autism group to a CA-matched typically developing group. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 33 publications
3
69
0
3
Order By: Relevance
“…Dawson, Meltzoff, Osterling, & Rinaldi, 1998; G. Dawson et al, 2002; Griffith, Pennington, Wehner, & Rogers, 1999; Stahl & Pry, 2002; Yerys, Hepburn, Pennington, & Rogers, 2007); however executive function deficits are reported in childhood (McEvoy, Rogers, & Pennington, 1993; Pellicano, 2010; Yerys, Wolff, Moody, Pennington, & Hepburn, 2012) and persist or increase into adolescence and adulthood in visual spatial working memory (Luna et al, 2007; O’Hearn et al, 2008), response inhibition (Luna et al, 2007; O’Hearn et al, 2008), planning (Pellicano, 2010; Wallace, Silvers, Martin, & Kenworthy, 2009), and set shifting (Ozonoff et al, 2004; Rosenthal et al, 2013), the present study’s preliminary observation of a more complete “catch up” to TDCs is therefore potentially interesting. As discussed above, effortful analogical reasoning may provide a cognitive ability to leverage in teaching new skills to adolescents and young adults with ASD to help them cope with the increasing complexity of their social and academic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Dawson, Meltzoff, Osterling, & Rinaldi, 1998; G. Dawson et al, 2002; Griffith, Pennington, Wehner, & Rogers, 1999; Stahl & Pry, 2002; Yerys, Hepburn, Pennington, & Rogers, 2007); however executive function deficits are reported in childhood (McEvoy, Rogers, & Pennington, 1993; Pellicano, 2010; Yerys, Wolff, Moody, Pennington, & Hepburn, 2012) and persist or increase into adolescence and adulthood in visual spatial working memory (Luna et al, 2007; O’Hearn et al, 2008), response inhibition (Luna et al, 2007; O’Hearn et al, 2008), planning (Pellicano, 2010; Wallace, Silvers, Martin, & Kenworthy, 2009), and set shifting (Ozonoff et al, 2004; Rosenthal et al, 2013), the present study’s preliminary observation of a more complete “catch up” to TDCs is therefore potentially interesting. As discussed above, effortful analogical reasoning may provide a cognitive ability to leverage in teaching new skills to adolescents and young adults with ASD to help them cope with the increasing complexity of their social and academic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some prior studies on very young, low cognitively functioning preschoolers with ASD (mean age of 33 months and up) showed no deficits on EF measures of inhibition, cognitive shifting, and working memory (Griffith et al 1999;Rutherford and Rogers 2003;Yerys et al 2007); yet, by 6 years of age, the majority of studies concerning EF in ASD reported deficits, in both high and low intellectually functioning samples (Corbett et al 2009;Shu et al 2001;Pellicano 2007;Yerys et al 2009). In the current study of cognitively able preschoolers, we did find significant differences from 36 months onwards, both on planning and cognitive shifting tasks, thus underscoring the need to examine the age when children with ASD actually ''grow into'' an EF deficit (Pellicano 2007).…”
Section: Group Differences and Similarities In Ef And Tom Abilitiesmentioning
confidence: 98%
“…Interestingly, the few existing studies concerning EF in very young preschool-age children with ASD (age 33 months and up), which examined mostly preschoolers with lower intellectual functioning, generally yielded no significant differences between the ASD group and peers with typical development or peers with developmental delay (Griffith et al 1999;Rutherford and Rogers 2003;Yerys et al 2007). One study of older preschoolers with ASD [chronological age (CA) = 64.6 months] who had low cognitive functioning [receptive language mental age (MA) = 30.4 months] found a significant delay on EF tasks (rule learning ability, working memory, and inhibition) in comparison to peers with down syndrome (CA = 65.3; receptive language MA = 27.3 months) and to typical peers (CA = 30.9; receptive language MA = 32.4 months) (Dawson et al 1998).…”
Section: Ef Capabilitiesmentioning
confidence: 99%
“…Outras investigações também têm sugerido comprometimento destas habilidades nos quadros de transtorno de aprendizagem, especificamente, a dislexia (Beneventi et al, 2010;Reiter et al, 2005;Salgado et al, 2008) e a discalculia (Argollo, 2008;Balbi, 2008;McLean & Hitch, 1999 (Yerys et al, 2007).…”
Section: Algumas Evidências De Alterações Executivas Em Crianças Com unclassified